Znaczenie utraty wartości aktywów w wycenie przedsiębiorstw w procesach fuzji i przejęć - Herdan, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The globalization of economy leads to the more and more free flow of capital and cause that mergers and acquisitions are the characteristic features of the XXI centuries economies. The main goals of mergers and acquisitions processes is achieving the new additional benefits often named as a synergy effect. The complexity and uncertainty of this processes cause that they often do not achieve the expected results. In many cases it is difficult to univocally tell why. The proper estimation of financial report information has the significant influence on the correctness of the valuation. The impairment of assets may have the direct or indirect influence on the valuation process. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 155-165